Molecular remission and response patterns in patients with mutant-IDH2 acute myeloid leukemia treated with enasidenib - Stein, EM; Dinardo, CD; Fathi, AT; Pollyea, DA; Stone, RM; Altman, JK; Roboz, GJ; Patel, MR; Collins, R; Flinn, IW; Sekeres, MA; Stein, AS; et al. (American Society of Hematology, 2018)
Approximately 8% to 19% of patients with acute myeloid leukemia (AML) have isocitrate dehydrogenase-2 (IDH2) mutations, which occur at active site arginine residues R140 and R172. IDH2 mutations produce an oncometabolite, 2-hydroxyglutarate (2-HG), which leads to DNA and histone hypermethylation and impaired hematopoietic differentiation. Enasidenib is an oral inhibitor of mutant-IDH2 proteins. This first-in-human phase 1/2 study evaluated enasidenib doses of 50 to 650 mg/d, administered in continuous 28-day cycles, in patients with mutant-IDH2 hematologic malignancies. Overall, 214 of 345 patients (62%) with relapsed or refractory (R/R) AML received enasidenib, 100 mg/d. Median age was 68 years. Forty-two patients (19.6%) attained complete remission (CR), 19 patients (10.3%) proceeded to an allogeneic bone marrow transplant, and the overall response rate was 38.8% (95% confidence interval [CI], 32.2-45.7). Median overall survival was 8.8 months (95% CI, 7.7-9.6). Response and survival were comparable among patients with IDH2-R140 or IDH2-R172 mutations. Response rates were similar among patients who, at study entry, were in relapse (37.7%) or were refractory to intensive (37.5%) or nonintensive (43.2%) therapies. Sixty-six (43.1%) red blood cell transfusion–dependent and 53 (40.2%) platelet transfusion–dependent patients achieved transfusion independence. The magnitude of 2-HG reduction on study was associated with CR in IDH2-R172 patients. Clearance of mutant-IDH2 clones was also associated with achievement of CR. Among all 345 patients, the most common grade 3 or 4 treatment-related adverse events were hyperbilirubinemia (10%), thrombocytopenia (7%), and IDH differentiation syndrome (6%). Enasidenib was well tolerated and induced molecular remissions and hematologic responses in patients with AML for whom prior treatments had failed. The study is registered at www.clinicaltrials.gov as #NCT01915498.